Perfluoroalkyl and polyfluoroalkyl substances, bisphenol and paraben compounds in dust collected from residential homes in Klang Valley, Malaysia - Mohamad Haron, Didi Erwandi; Yoneda, Minoru; Hod, Rafidah; A. Wahab, Muhammad Ikram; Aziz, Mohd Yusmaidie (Taylor and Francis Group, 2022)
Endocrine disrupting chemicals (EDCs) are a growing global concern due to their widespread use and potential harm to human and animal health. Several EDCs have been linked to cancer, obesity, and diabetes in children and adults. EDCs come from manufacturers or everyday products like cookware, textile, cosmetic, furniture, and plastic. Some EDCs are volatile and may be inhaled by the inhabitants where indoor exposure to EDCs is considered worse than outdoor exposure due to the limited and confined area allowing dermal contact and ingestion of EDCs. During the COVID-19 pandemic in 2020–2021, all Malaysians were confined to their homes, prompting the goal of this study to investigate EDCs in household dust collected from Klang Valley homes. A total of 57 dust samples were collected, filtered, and extracted using methanol. EDCs including perfluoroalkyl and polyfluoroalkyl substances (PFAS), bisphenol and parabens were identified and quantified in dust samples by liquid chromatography mass tandem spectrometry (LCMS/MS). The presence of perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), butylparaben (BuP), methylparaben (MeP), ethylparaben (EtP), and propylparaben (PrP) was detected in 50–100% of dust samples, with range of concentration of 0.31–3693.96 ng/g, indicating that these compounds are common in indoor dust. Methylparaben was the most prevalent EDC in collected dust samples with mean concentration at 148. 18 ng/g, accounting for 54% of the concentration distribution, followed by BuP and PFOA. There were regional differences in EDC profiles, with higher PFAS and paraben levels in urban areas such as Putrajaya, Kuala Lumpur, and Petaling. The estimated daily intake (EDI) of EDCs from indoor dust ingestion varied by age, with infants having a significantly higher EDI (p < .01) than children and adults. Despite safe for consumption (Hazard Quotient, HQ < 1), these findings provide a baseline for assessing PFAS, bisphenol, and paraben in indoor dust from Malaysian homes.